Validitas LKPD Berbasis Argumentasi dengan Bantuan Web Energy4Me untuk Meningkatkan Kemampuan Pemecahan Masalah pada Peserta Didik SMA - Maysaputri, Yunita; Admoko, Setyo (IPF: Inovasi Pendidikan Fisika, 2024)
This research was to find the validity of the worksheet based on argumentation assisted by the energy4me web to improve problem-solving abilities on alternative energy material. This research is using the R&D method with a 4D development model. This model use four stages, namely define, design, develop and disseminate. The validity of the worksheet is assessed from two aspects, namely content and construction. The data collection technique used in this research includes validation of worksheet obtained from the results of three validators. The instrument used in this research is the worksheet based on argumentation assisted by the energy4me web to improve problem solving abilities. The data obtained was analyzed through an assessment of the LKPD which was developed using quantitative descriptive methods. This data was obtained from the results of the validity of worksheets which had been validated by three validators, namely two physics expert lecturers and a high school physics teacher. The results of the validity analysis of the worksheet show that the overall average score obtained in the content aspect is 97.91% in the validest category, while in the construction aspect it is 97.22% in the very valid category. Based on these results, the average value of validity for all aspects was found to be 97.74% in the validest category, so it can be concluded that the worksheet based on argumentation assisted by the energy4me web to improve problem solving abilities in alternative energy materials is suitable for use and application in the learning process.   Keywords: Workssheet, Problem-Solving Ability, Alternative Energy